A positive electrode active material, a lithium ion secondary battery
Patent Information
- Application Number
- CN202611073173.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-13
AI Technical Summary
然而,该材料在实际应用中面临双重技术瓶颈:一是结构稳定性差,长期循环过程中易发生晶格氧释放、层状结构向尖晶石相或岩盐相不可逆转变,导致电压衰减和容量快速下降;二是界面兼容性差,与液态电解液或固态电解质接触时,界面离子传输效率低,且容易发生副反应,形成高阻抗界面层,严重制约电池的倍率性能和循环寿命
[0037]本发明提供的正极活性材料兼具高结构稳定性和优异的界面兼容性,用于电池后,能够显著提升电池性能。通过采用包括富锂锰基内核、设置于富锂锰基内核至少部分表面的快离子导体包覆层,并使富锂锰基内核掺杂聚阴离子且其表面的聚阴离子浓度C1小于中心的聚阴离子浓度C2的技术方案,能够使正极活性材料兼顾在高电压条件下的结构稳定性以及材料表面与固态电解质接触时的离子传输需求,降低氧释放、过渡金属迁移、相变及界面阻抗带来的不利影响,进而提升电池的首效、循环稳定性和倍率性能。
Smart Images

Figure CN122907616A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary batteries, and more particularly to a positive electrode active material and a lithium-ion secondary battery. Background Technology
[0002] With the advancement of global energy structure transformation, the demand for high-energy-density and high-safety batteries for new energy vehicles and large-scale energy storage systems is becoming increasingly urgent.
[0003] Lithium-rich manganese-based cathode materials are considered candidate materials for next-generation high-energy-density batteries due to their advantages of high theoretical specific capacity and low cost. However, this material faces two technical bottlenecks in practical applications: First, poor structural stability, which easily leads to lattice oxygen release and irreversible transformation of the layered structure into spinel or rock salt phases during long-term cycling, resulting in voltage decay and rapid capacity decline; second, poor interfacial compatibility, with low interfacial ion transport efficiency and easy side reactions when in contact with liquid electrolytes or solid electrolytes, forming a high-resistivity interfacial layer, which seriously restricts the rate performance and cycle life of the battery.
[0004] Therefore, developing lithium-rich manganese-based cathode active materials that combine high structural stability and excellent interfacial compatibility is key to breaking through the commercialization bottleneck of next-generation high-energy-density batteries. Summary of the Invention
[0005] This invention provides a positive electrode active material that combines high structural stability and excellent interface compatibility, which can significantly improve battery performance when used in batteries.
[0006] This invention provides a lithium-ion secondary battery comprising the above-mentioned positive electrode active material, which has excellent cycle stability and rate performance.
[0007] This invention provides a positive electrode active material, comprising a lithium-rich manganese-based core and a fast ion conductor coating layer disposed on at least a portion of the surface of the lithium-rich manganese-based core, wherein the lithium-rich manganese-based core is doped with polyanions;
[0008] Wherein, the polyanion concentration on the surface of the lithium-rich manganese-based core is C1, and the polyanion concentration at the center of the lithium-rich manganese-based core is C2, where C1 < C2.
[0009] In the positive electrode active material described above, the sphericity of the lithium-rich manganese-based core is 0.7~0.95;
[0010] The center of the lithium-rich manganese-based core is Q, and the equivalent radius is R;
[0011] The lithium-rich manganese-based core includes an internal region and a surface region;
[0012] Wherein, the inner region is the region with Q as the starting point and 1 / 2R as the radius, and the surface region is the region surrounding the inner region and extending from the surface of the inner region to the surface of the lithium-rich manganese-based core.
[0013] The average concentration of polyanions in the internal region is A, and the average concentration of polyanions in the surface region is B, where 1 < A: B ≤ 10.
[0014] As mentioned above, the positive electrode active material A has a concentration of 4000-10000 ppm; and B has a concentration of 1000-5000 ppm.
[0015] As described above, in the positive electrode active material, the surface area coverage of the fast ion conductor coating layer is 1% to 50%.
[0016] And / or, the average thickness of the fast ion conductor coating layer is 20~40 nm;
[0017] And / or, the ionic conductivity of the fast ion conductor coating layer is >10. -4 S / cm;
[0018] And / or, the fast ion conductor coating layer includes at least one of lithium ion conductors, sodium ion conductors, oxygen ion conductors, and proton conductors.
[0019] As described above, in the positive electrode active material, the chemical composition of the polyanion in the lithium-rich manganese-based core includes (X... 1 m O p ) n- ; where X 1 The element includes at least one of P, S, As, Mo, Si, B, W, and Al;
[0020] m is 1~18, p is 4~42, and n is 2~10.
[0021] The positive electrode active material as described above, wherein the lithium-rich manganese-based core further includes X 2 Element, the X 2 The element includes at least one of P, B, S, Si, and Ti, wherein X 2 Element and the X 1 The elements are different;
[0022] The lithium-rich manganese-based core satisfies at least one of the following conditions:
[0023] (1) Based on the lithium-rich manganese-based core, the X 2 The doping level of the element is 100~6000ppm;
[0024] (2) The X-rays on the surface of the lithium-rich manganese-based core 2The element concentration is C3, and the X at the center of the lithium-rich manganese-based core... 2 The concentration of the element is C4, and C3 < C4.
[0025] In the positive electrode active material described above, the sphericity of the lithium-rich manganese-based core is 0.7~0.95;
[0026] The center of the lithium-rich manganese-based core is Q, and the equivalent radius is R;
[0027] The lithium-rich manganese-based core includes an internal region and a surface region; wherein, the internal region is a region with Q as the starting point and 1 / 2R as the radius, and the surface region is a region surrounding the internal region and extending from the surface of the internal region to the surface of the lithium-rich manganese-based core.
[0028] X of the internal region 2 The average concentration of the element is a, and the X of the surface region is... 2 The average concentration of the element is b, and 1 < a / b ≤ 10.
[0029] As mentioned above, the positive electrode active material has a concentration of 500~1000ppm and a concentration of 100~500ppm.
[0030] The positive electrode active material described above, wherein the lithium-rich manganese-based core satisfies at least one of the following conditions:
[0031] (1) The particle size Dv50 of the lithium-rich manganese-based core is 2~5μm, and the SPAN value is 0.5~1.8;
[0032] (2) The lithium-rich manganese-based core is composed of N primary particles, where N≥2, and the average particle size of the primary particles is 0.1~1.0μm;
[0033] (3) The specific surface area of the positive electrode active material is 1~4m². 2 / g;
[0034] (4) The resistivity of the positive electrode active material powder is ≥10. -7 S / Cm.
[0035] In another aspect, the present invention provides a lithium-ion secondary battery, comprising a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active layer disposed on at least one side surface of the positive electrode current collector in the thickness direction, the positive electrode active layer comprising a positive electrode active material; the positive electrode active material comprising the positive electrode active material as described above;
[0036] The lithium-ion secondary battery includes any one of the following: all-solid-state battery, semi-solid-state battery, and liquid battery.
[0037] The positive electrode active material provided by this invention possesses both high structural stability and excellent interfacial compatibility, which can significantly improve battery performance when used in batteries. By employing a technical solution comprising a lithium-rich manganese-based core, a fast-ion conductor coating layer disposed on at least a portion of the surface of the lithium-rich manganese-based core, and doping the lithium-rich manganese-based core with polyanions, wherein the polyanion concentration C1 on its surface is less than the polyanion concentration C2 at the center, the positive electrode active material can balance structural stability under high voltage conditions with the ion transport requirements when the material surface contacts the solid electrolyte. This reduces the adverse effects of oxygen release, transition metal migration, phase transition, and interfacial impedance, thereby improving the battery's initial efficiency, cycle stability, and rate performance. Attached Figure Description
[0038] Figure 1 This is a schematic diagram of the lithium-rich manganese-based core structure in a specific embodiment of the present invention;
[0039] Figure 2 The infrared spectrum of the positive electrode active material provided in Embodiment 1 of the present invention;
[0040] Figure 3 This is a scanning electron microscope image of the positive electrode active material provided in Embodiment 1 of the present invention;
[0041] Figure 4 This is a scanning electron microscope image of the positive electrode active material provided in Comparative Example 1 of the present invention.
[0042] Figure label:
[0043] 1-Internal region; 2-Surface region; 3-Polyanion; Q-Center of lithium-rich manganese-based core. Detailed Implementation
[0044] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples of apparatuses and methods consistent with some aspects of the invention as detailed in the appended claims.
[0045] The poor structural stability and poor interface compatibility of lithium-rich manganese-based cathode materials severely restrict the rate performance and cycle life of batteries.
[0046] Existing improvement technologies often focus only on one aspect: structural stability and interface compatibility. If only the internal stability of the material is enhanced, interface transport issues will still limit overall performance; if only the surface interface is improved, the deterioration of the internal structure of the material will exacerbate interface failure. Therefore, existing solutions generally struggle to achieve a balance between high capacity, high structural stability, and low interface impedance, making it difficult to meet the simultaneous requirements of high energy density and high safety in batteries.
[0047] The inventors believe that the crystal structure can be stabilized through the gradient distribution of polyanions from the inside out, while reducing surface stress concentration. Building on this, a fast ion conductor coating layer is further introduced, utilizing its high ionic conductivity and chemical stability to construct continuous interfacial channels, thereby simultaneously improving the material's structural stability and interfacial transport efficiency.
[0048] Based on this, the present invention provides a positive electrode active material, comprising a lithium-rich manganese-based core and a fast ion conductor coating layer disposed on at least a portion of the surface of the lithium-rich manganese-based core, wherein the lithium-rich manganese-based core is doped with polyanions.
[0049] The concentration of polyanions on the surface of the lithium-rich manganese-based core is C1, and the concentration of polyanions in the center of the lithium-rich manganese-based core is C2, where C1 < C2.
[0050] The positive electrode active material in this invention can be used in all-solid-state batteries, semi-solid-state batteries, and liquid batteries.
[0051] In this system, the lithium-rich manganese-based core serves as the primary lithium storage host, preferably a layered lithium-rich manganese-based oxide, such as a composite layered system represented as xLi2MnO3·(1-x)LiM1O2, where M1 can include at least one of Ni, Co, and Mn. This type of material exhibits high reversible capacity, but during high-voltage charge-discharge processes, it is prone to problems such as excessive lattice oxygen activation, oxygen release, transition metal migration, and the evolution of the layered structure into a spinel or rock salt phase.
[0052] This invention does not simply protect the surface, but introduces polyanion doping into the core and creates a concentration distribution of polyanions that decreases from the center to the surface within the particle. This provides stronger structural support to the core while maintaining a more suitable lithium-ion migration environment in the area near the surface.
[0053] It is understandable that the lithium-rich manganese-based core may have a spherical or other irregular spherical shape. In this case, the center of the lithium-rich manganese-based core refers to its centroid, which can be determined using transmission electron microscopy combined with image analysis software.
[0054] The concentration of polyanions at the center and surface of the lithium-rich manganese-based core can be detected using methods commonly used in the field.
[0055] In some embodiments, the distribution of polyanions in the lithium-rich manganese-based core can be detected using argon ion milling-scanning electron microscopy-energy dispersive spectroscopy (CP-SEM-EDS), including the following steps:
[0056] The positive electrode active material is mixed with polyvinylidene fluoride (PVDF) and then coated on both sides of aluminum foil. After drying and rolling, the positive electrode sheet is obtained and sent for CP-SEM-EDS testing. The content of polyanions in various parts of the lithium-rich manganese-based core is tested by EDS line scan or area scan of the particle cross section.
[0057] In other embodiments, the distribution of polyanions in the lithium-rich manganese-based core can be detected by electron probe microanalysis (EPMA).
[0058] Since the fast ion conductor coating has little effect on the elemental distribution in the lithium-rich manganese-based core, the positive electrode active material can be directly detected, which is equivalent to the elemental distribution in the lithium-rich manganese-based core.
[0059] Wherein, C1 represents the polyanion concentration in the surface region of the lithium-rich manganese-based core, and C2 represents the polyanion concentration in the central region of the lithium-rich manganese-based core. Polyanion units typically possess strong M2-OX... 1 Bonding, where M2 represents at least one of Ni, Co, and Mn; X 1 P, S, Si, and B represent the central elements that form the anionic framework. The high concentration of polyanions in the central region of the lithium-rich manganese-based core is beneficial for improving the lattice oxygen binding ability and stabilizing the arrangement of transition metal layers. However, if the surface region is doped too much, it may increase the local structural rigidity and increase the ion diffusion barrier in the solid-solid contact region. Therefore, adopting a gradient design with C1 less than C2 can simultaneously take into account structural stability and transport performance.
[0060] In some embodiments, the polyanion concentration decreases gradually from the center of the lithium-rich manganese-based core to its surface. It is understood that slight fluctuations in the polyanion concentration may occur during this process.
[0061] In other embodiments, the concentration of polyanions first decreases and then remains relatively stable from the center of the lithium-rich manganese-based core to the surface of the lithium-rich manganese-based core.
[0062] In terms of preparation, lithium-rich manganese-based cores can be prepared by co-precipitation-lithiation sintering. To form a polyanion concentration gradient of C1 < C2, a staged introduction of doping sources can be adopted. For example, the main polyanion source can be mixed in before precursor preparation or lithiation, so that the polyanions preferentially dissolve inside the particles, and then additional surface enrichment can be avoided in subsequent surface treatment processes. Alternatively, a heat treatment method that controls the diffusion depth can be used, that is, a limited diffusion time and diffusion temperature are applied after lithiation sintering, so that the polyanion source only partially enters the surface layer, thereby keeping the doping level in the core higher than that in the surface region. Alternatively, a polyanion-rich central precursor and a relatively low polyanion outer layer precursor can be formed by spray granulation, and then gradient particles can be obtained by sintering.
[0063] In some embodiments, the sintering temperature can be controlled between 750℃ and 980℃, and the holding time can be between 5h and 20h. If the temperature is too low, the polyanions are difficult to stably enter the crystal lattice, the gradient distribution is not obvious, and the crystallinity of the layered structure is insufficient. If the temperature is too high or the holding time is too long, the polyanions are prone to excessive diffusion to the surface, weakening the difference between C1 and C2, and even causing lithium volatilization and abnormal particle growth, which is not conducive to the uniform formation of the subsequent coating layer. Therefore, by controlling the heat treatment window, the doping depth, crystal quality, and particle morphology can be synergistically optimized.
[0064] A fast-ion conductor coating layer disposed on at least part of the surface of a lithium-rich manganese-based core is used to improve the interfacial ion transport conditions when the positive electrode active material is in contact with the solid electrolyte.
[0065] The fast ion coating layer is disposed on at least part of the surface of the lithium-rich manganese-based core, which means that it can be a fully coated structure or a locally continuous (e.g., island-like) coating network depending on the particle contact configuration.
[0066] Fast ion conductor coatings can be formed by dry mixing combined with low-temperature sintering.
[0067] In some embodiments, the fast ion conductor coating layer can be prepared by a method including the following steps: first, dispersing the gradient-doped lithium-rich manganese-based core in alcohol, water or a mixture thereof, then adding a precursor salt containing a lithium source and fast ion conductor framework elements, so that it is adsorbed and deposited on the particle surface, and then heat-treated at 200°C to 700°C to form an oxide fast ion conductor coating layer.
[0068] The positive electrode active material provided by this invention establishes a composite functional structure that balances bulk stability and interfacial transport through the synergistic design of polyanion gradient doping in a lithium-rich manganese-based core and an external fast-ion conductor coating layer. The high polyanion concentration at the center of the lithium-rich manganese-based core enhances the stability of the oxygen framework and the transition metal coordination environment in the central region, suppressing phase transitions and oxygen release induced deep within the positive electrode active material during high-voltage delithiation. The lower polyanion concentration on the surface of the lithium-rich manganese-based core avoids excessive passivation of the surface layer, maintaining low lithium-ion migration resistance. Simultaneously, the fast-ion conductor coating layer constructs continuous or quasi-continuous lithium-ion transport channels on the outer surface, reducing direct chemical conflict between the lithium-rich manganese-based core and the electrolyte, resulting in a more stable interface with lower impedance ion exchange boundaries. This allows the positive electrode active material to withstand redox stress under high-voltage conditions during charge and discharge while maintaining effective contact with the electrolyte or electrolyte solution, thereby reducing irreversible capacity loss in the first cycle, slowing impedance rise during cycling, and improving rate performance and long-term cycle life.
[0069] In some embodiments of the present invention, the sphericity of the lithium-rich manganese-based core is 0.7 to 0.95;
[0070] like Figure 1 As shown, the center of the lithium-rich manganese-based core is Q, and the equivalent radius is R;
[0071] The lithium-rich manganese-based core includes an internal region 1 and a surface region 2;
[0072] Among them, the inner region 1 is the region with Q as the starting point and 1 / 2R as the radius, and the surface region 2 is the region surrounding the inner region 1 and extending from the surface of the inner region 1 to the surface of the lithium-rich manganese-based core.
[0073] The average concentration of polyanion 3 in the internal region 1 is A, and the average concentration of polyanion 3 in the surface region 2 is B, where 1 < A: B ≤ 10.
[0074] The sphericity of the lithium-rich manganese-based core in this invention can be tested through the following process:
[0075] Microscopic images of at least five fields of view were randomly acquired using a field emission scanning electron microscope at magnification of 500–5000x. At least 200 silicon-carbon material particles were counted. The SEM images were imported into image analysis software, and contour recognition was performed on each particle. The projected perimeter S and maximum diameter L (i.e., the maximum distance between any two points in the particle's projected contour) were measured. The sphericity of the lithium-rich manganese-based core was calculated using the following formula:
[0076] Sphericity = S / (L*Π).
[0077] Among them, the closer the sphericity is to 1, the closer it is to an ideal sphere.
[0078] It should be noted that although the positive electrode active material includes a lithium-rich manganese-based core and a fast-ion coating layer disposed on at least part of the surface of the lithium-rich manganese-based core, the effect of the fast-ion coating layer on the sphericity of the lithium-rich manganese-based core is negligible due to the low thickness of the fast-ion coating layer.
[0079] Therefore, the sphericity of the positive electrode active material obtained from the test can be equated to the sphericity of the lithium-rich manganese-based core.
[0080] In this invention, the equivalent radius R of the lithium-rich manganese-based core is determined as follows: First, a high-resolution two-dimensional projection image of the lithium-rich manganese-based core particles is obtained by scanning electron microscopy (SEM) or transmission electron microscopy (TEM); then, the projection outline of the particles is delineated and its actual projection area A is extracted using professional image analysis software; finally, the equivalent radius R of the lithium-rich manganese-based core is calculated based on the equal area circle model.
[0081] The average concentration of polyanions in the internal region 1 refers to the content of polyanions per unit volume in the internal region, while the average concentration of polyanions in the surface region 2 refers to the content of polyanions per unit volume in the surface region.
[0082] In some embodiments, A and B can be detected by a detection method including the following steps:
[0083] The cross-section of the lithium-rich manganese-based core is tested using an electron probe or SEM-EDS. The internal and surface regions are selected using image processing software, and the average element content of all pixels in these two selected regions is automatically calculated to obtain A and B.
[0084] In detail, A:B includes, but is not limited to, a range consisting of 1.1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any two of them.
[0085] By controlling the A:B ratio within a range greater than 1 and not exceeding 10, the higher polyanion concentration in the internal region can improve lattice stability and slow down irreversible structural evolution, while the lower polyanion concentration in the surface region helps maintain the continuity of ion migration with the fast ion conductor coating layer. Thus, this gradient structure, combined with high sphericity, can simultaneously improve the integrity of the cathode active material, the uniformity of interfacial contact, and the lithium-ion transport efficiency, thereby improving initial efficiency, cycle life, and rate performance.
[0086] In some embodiments of the present invention, A is 4000-10000ppm; B is 1000-5000ppm.
[0087] That is, the average concentration A of polyanions in the internal region includes, but is not limited to, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, 10000 ppm or any combination thereof; the average concentration of polyanions in the surface region includes, but is not limited to, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm or any combination thereof.
[0088] By controlling A at 4000-10000ppm and B at 1000-5000ppm, the higher A value in the internal region can enhance the local strong covalent bond network, exert a stronger constraint on lattice oxygen, and suppress oxygen release, transition metal migration and phase transition during high-voltage cycling; while the lower B value in the surface region can avoid lattice stress concentration caused by excessive doping of the outer layer, maintain the integrity of the particle surface, and provide a more stable bonding basis for the subsequent fast ion conductor coating layer.
[0089] In some embodiments of the present invention, the surface area coverage of the fast ion conductor coating layer is 1% to 50%.
[0090] In this invention, the coverage rate of the fast ion conductor coating layer refers to the area coverage rate, that is, the proportion of the surface area of the lithium-rich manganese-based core covered by the fast ion conductor coating layer based on the overall surface area of the lithium-rich manganese-based core.
[0091] The coating efficiency of fast ion conductor coatings can be detected using methods commonly used in the field, such as scanning electron microscopy combined with image analysis.
[0092] In detail, the coverage of the fast ion conductor coating includes, but is not limited to, a range of 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any two of these.
[0093] When the coverage of the fast ion conductor coating layer is within the above range, it can effectively protect the surface of the lithium-rich manganese-based core by forming a fast ion conductor coating layer, isolate the lithium-rich manganese-based core from direct contact with the electrolyte, suppress interfacial side reactions, lattice oxygen release and transition metal dissolution, and ensure structural stability under high voltage cycling. It can also provide a fast lithium-ion transport channel by utilizing the conductivity of the fast ion conductor, thereby improving rate performance.
[0094] In some embodiments of the present invention, the average thickness of the fast ion conductor coating layer is 20-40 nm.
[0095] The average thickness of the fast ion conductor coating can be determined using detection methods commonly used in the field. For example, high-resolution transmission electron microscopy can be used for testing.
[0096] In detail, the average thickness of the fast ion conductor coating includes, but is not limited to, a range of 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, or any combination thereof.
[0097] When the average thickness of the fast ion conductor coating is within the above range, the fast ion conductor can form a continuous lithium ion migration channel, ensuring rapid lithium ion migration without hindering the wettability of the electrolyte and the coating.
[0098] In some embodiments of the present invention, the ionic conductivity of the fast ion conductor coating layer is >10. -4 S / cm.
[0099] The ionic conductivity of the fast ion conductor coating can be detected using common detection methods in this field.
[0100] In some embodiments, the ionic conductivity of the fast ion conductor coating layer can be detected by a method including the following steps:
[0101] Fast-ion conductor powders (such as oxide and sulfide electrolytes) are pressed into dense circular discs in a mold. The diameter (D) and thickness (L) of the sample are precisely measured to calculate the cross-sectional area A and geometric factor. Blocking electrodes are fabricated on both sides of the sample. After the test system is set up, the test frequency range is set to 1MHz to 0.1Hz, and a small signal perturbation is used under constant temperature conditions. The test is started, and the instrument automatically scans the set frequency range, recording the real part (Z′) and imaginary part (−Z′) of the impedance at each frequency. A complex plane diagram is plotted with the real part Z′ as the horizontal axis and the negative imaginary part −Z′ as the vertical axis to construct an equivalent circuit. The bulk resistance (R) is extracted from the fitting results. b The ionic conductivity is calculated using the following formula:
[0102] σ=L / (R) b *A) Where: σ: ionic conductivity (S / cm), L: sample thickness (cm), A: contact area between electrode and electrolyte (cm²), for circular samples A=π(D / 2) 2 Rb: Bulk resistance (Ω) obtained from the fitting.
[0103] In detail, the ionic conductivity of the fast ion conductor coating layer includes, but is not limited to, 10. -4 S / cm, 2×10 -4 S / cm, 4×10 -4 S / cm, 6×10 -4 S / cm, 8×10 -4 S / cm, 1×10 -3 S / cm or any other value greater than 10-4 Range of S / cm.
[0104] When the ionic conductivity of the fast ion conductor coating layer is within the above range, it can provide a low-impedance fast diffusion channel for lithium ions, enhance the lithium ion migration rate, and at the same time, the high conductivity coating layer can effectively improve the interface dynamics under high voltage conditions, suppress continuous side reactions and enhance the stability of the cathode structure, thereby ensuring the battery cycle life.
[0105] In some embodiments of the present invention, the fast ion conductor coating layer includes at least one of lithium ion conductor, sodium ion conductor, oxygen ion conductor, and proton conductor.
[0106] In some embodiments of the present invention, the chemical composition of the polyanion in the lithium-rich manganese-based core includes (X... 1 m O p ) n- ; where X 1 The element includes at least one of P, S, As, Mo, Si, B, W, and Al;
[0107] m is 1~18, p is 4~42, and n is 2~10.
[0108] The chemical composition of polyanions in a lithium-rich manganese-based core can be detected using methods commonly found in the art. For example, in some embodiments, infrared spectroscopy is used to detect the chemical composition of polyanions in a lithium-rich manganese-based core.
[0109] In detail, m includes, but is not limited to, a range consisting of 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or any two of them; p includes, but is not limited to, a range consisting of 4, 5, 10, 15, 20, 25, 30, 35, 40, 42, or any two of them; n includes, but is not limited to, a range consisting of 2, 3, 4, 5, 6, 7, 8, 9, 10, or any two of them.
[0110] In this embodiment, the polyanions in the lithium-rich manganese-based core include (X... 1 m O p ) n- The existence of this form indicates that it is not a single simple anion, but rather a multi-oxygen anion unit with a certain polymeric structure. By using X... 1 Limited to at least one of P, S, As, Mo, Si, B, W, and Al, it can enable the polyanion to form different coordination environments.
[0111] In some embodiments, the polyanionic compound of the lithium-rich manganese-based core includes phosphates, such as Na3PO4, Al3PO4, (NH4)3PO4; sulfates, such as Na2SO4, Al2(SO4)3, (NH4)2SO4; molybdates, such as Na2MoO4; silicates, such as Na4SiO4; borates, such as Na2B4O7; or tungstates, such as Na2WO4, thereby enhancing the binding ability with the lithium-rich manganese-based lattice and improving the binding effect on lattice oxygen.
[0112] By controlling m to 1 to 18, p to 4 to 42, and n to 2 to 10, the polyanion can possess sufficient structural stabilization capability while avoiding damage to the bulk lattice integrity due to excessively large anion units or excessively high charges. Preferably, medium-polymerization units that are easier to embed in the lattice and have stable coordination can be selected to balance bulk stability and ion migration. This process enables the construction of a stable local framework within the lithium-rich manganese-based core, allowing the material to better maintain its crystal structure during charge-discharge cycles, thereby reducing irreversible losses in the first cycle and slowing down capacity decay, ultimately improving cycle life and structural reliability under high voltage conditions.
[0113] In some embodiments, the lithium-rich manganese-based core also includes X 2 Element, X 2 The elements include at least one of P, B, S, Si, and Ti, and X 2 The element is different from element X;
[0114] The lithium-rich manganese-based core satisfies at least one of the following conditions:
[0115] (1) Based on a lithium-rich manganese-based core, X 2 The doping level of the element is 100~6000ppm;
[0116] (2) X on the surface of the lithium-rich manganese-based core 2 The element concentration is C3, and the center of the lithium-rich manganese-based core is X. 2 The concentration of the element is C4, and C3 < C4.
[0117] The X 2 Elements can enter the lattice, grain boundaries, or local enrichment regions, and by using their different bond energy characteristics and coordination modes, they can adjust the local stress and electronic structure of the transition metal layer, and suppress the migration of transition metals and lattice oxygen instability under high voltage.
[0118] Among them, for condition (1), based on the lithium-rich manganese-based core, X 2 The doping level of the element is 100~6000ppm.
[0119] X can be detected using detection methods commonly used in this field. 2The doping level of an element. For example, X can be detected by ICP-MS. 2 The amount of elemental doping.
[0120] In detail, X 2 The doping amount of the element includes, but is not limited to, 100ppm, 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm or any combination thereof.
[0121] X based on lithium-rich manganese-based core 2 When the elemental doping concentration is controlled within the range of 500~6000ppm, it can be achieved in X 2 With elements occupying almost no active sites in the material, the stabilizing effect on the crystal structure of the material is fully utilized to achieve effective control of the material structure, avoid additional capacity loss, and ultimately effectively improve the first-cycle coulombic efficiency, long cycle life, and structural stability under high voltage operating conditions while fully preserving the intrinsic high specific capacity advantage of lithium-rich manganese-based materials, thus achieving synergistic optimization of material capacity and stability.
[0122] For condition (2), methods commonly used in the art can be employed to detect the surface X of the lithium-rich manganese-based core. 2 Elemental concentration and the central X of the lithium-rich manganese-based core 2 Element concentration.
[0123] For example, detection can be performed using argon ion polishing-scanning electron microscopy-energy dispersive spectroscopy (CP-SEM-EDS) or electron probe microanalysis (EPMA).
[0124] When the surface of the lithium-rich manganese-based core is X 2 The concentration of the element is C3, and the central X 2 When the concentration of element X is C4 and C3 < C4, it indicates that X... 2 The elements are centrally enriched in the radial direction, which makes the central region provide stronger structural support for the surface region, while the lower surface concentration helps to reduce interfacial stress and side reaction tendency when in contact with solid electrolytes.
[0125] In some embodiments, the sphericity of the lithium-rich manganese-based core is 0.7 to 0.95;
[0126] The center of the lithium-rich manganese-based core is Q, and the equivalent radius is R;
[0127] The lithium-rich manganese-based core includes an internal region and a surface region; the internal region is the area with Q as the starting point and 1 / 2R as the radius, and the surface region is the area surrounding the internal region and extending from the surface of the internal region to the surface of the lithium-rich manganese-based core.
[0128] X in the internal area 2 The average concentration of the element is a, and the surface region X 2 The average concentration of the element is b, and 1 < a / b ≤ 10.
[0129] The spatial scale of the lithium-rich manganese-based core is defined by its center Q and its equivalent radius R. The equivalent radius R can be determined as follows: First, a high-resolution two-dimensional projection image of the lithium-rich manganese-based core particle is obtained by scanning electron microscopy (SEM) or transmission electron microscopy (TEM); then, the projection outline of the particle is delineated and its actual projection area A is extracted using professional image analysis software; finally, the equivalent radius R of the lithium-rich manganese-based core is calculated based on the equal area circle model.
[0130] After dividing the core into an internal region and a surface region, the internal region, as the core area with a radius of 1 / 2R starting from Q, typically corresponds to the part with higher lattice stability requirements; the surface region is located outside the core and extends to the particle surface, directly participating in the contact with the coating layer and solid electrolyte, and is therefore more suitable for using a lower X. 2 Element concentration is used to reduce interfacial strain and side reactions.
[0131] Among them, X in the internal region 2 The average concentration of an element refers to the concentration of X per unit volume within the internal region. 2 The content of elements, and the X of the surface region. 2 The average concentration of an element refers to the concentration of X per unit volume of the surface region. 2 The content of elements.
[0132] In some embodiments, a and b can be detected by a detection method including the following steps:
[0133] The cross-section of the lithium-rich manganese-based core is tested using an electron probe or SEM-EDS. The internal and surface regions are selected using image processing software, and the average element content of all pixels in these two selected regions is automatically calculated to obtain a and b.
[0134] In detail, a / b includes, but is not limited to, a range consisting of 1.1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any two of them.
[0135] When a / b meets the above range, it means X 2The elements exhibit a gradient distribution that decreases from the inside to the outside along the radial direction. This ensures internal stabilization while avoiding lattice mismatch and internal stress accumulation caused by excessively steep gradients, achieving a balance between core structural stability and external surface interface adaptation. This, in turn, enhances the cycle stability, interface compatibility, and overall electrochemical performance of the cathode active material.
[0136] In some embodiments of the present invention, a is 500~1000ppm and b is 100~500ppm.
[0137] Specifically, a) includes, but is not limited to, a range of 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm or any two of these ranges; b) includes, but is not limited to, a range of 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm or any two of these ranges.
[0138] Maintaining the concentration of a at 500-1000 ppm can make the X-rays more prominent in the central region of the kernel. 2 Element enrichment enhances local lattice rigidity, suppressing transition metal migration, lattice oxygen release, and the transformation of layered structures to spinel or rock salt phases during high-voltage charging and discharging. Controlling b at 100–500 ppm avoids excessive surface doping that hinders ion diffusion and increases interfacial impedance, while providing a more suitable interfacial basis for subsequent fast ion conductor coatings.
[0139] In some embodiments of the present invention, the lithium-rich manganese-based core satisfies at least one of the following conditions:
[0140] (1) The particle size Dv50 of the lithium-rich manganese-based core is 2~5μm, and the SPAN value is 0.5~1.8;
[0141] (2) The lithium-rich manganese-based core is composed of N primary particles, where N≥2, and the average particle size of the primary particles is 0.1~1.0μm;
[0142] (3) The specific surface area of the positive electrode active material is 1~4m². 2 / g;
[0143] (4) The powder resistivity of the positive electrode active material is ≥10 -7 S / Cm.
[0144] Regarding condition (1), the particle size Dv50 of the lithium-rich manganese-based core refers to the median particle size of the lithium-rich manganese-based core, that is, the particle size value corresponding to when the cumulative particle size distribution of the lithium-rich manganese-based powder reaches 50%. The SPAN value refers to the quantitative index of the particle size distribution width, and the calculation formula is SPAN=(Dv90-Dv10) / Dv50, where D10, Dv50, and Dv90 represent the particle size values when the cumulative particle size distribution reaches 10%, 50%, and 90%, respectively. The larger the SPAN value, the wider the particle size distribution.
[0145] The particle size Dv10, Dv50 and Dv90 of lithium-rich manganese-based cores can be detected using methods commonly used in the field, thereby calculating the SPAN value, such as laser particle size distribution and sieving.
[0146] It is understandable that the positive electrode active material includes a fast ion conductor coating layer in addition to the lithium-rich manganese-based core. However, since the thickness of the fast ion coating layer is at the nanometer level, its influence on the micrometer-level particle size can be ignored. Therefore, the particle size Dv50 of the positive electrode active material obtained by the test can be equated with the particle size Dv50 of the lithium-rich manganese-based core.
[0147] In detail, the particle size Dv50 of the lithium-rich manganese-based core includes, but is not limited to, a range of 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or any two thereof; the SPAN value includes, but is not limited to, a range of 0.5, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 or any two thereof.
[0148] By controlling the Dv50 of the lithium-rich manganese-based core to 2~5μm and the SPAN to 0.5~1.8, the particle size can be moderate and the distribution concentrated, which is beneficial to improving the compaction density of the electrode, shortening the diffusion path of lithium ions inside the particles, and improving the contact uniformity between the solid electrolyte and the cathode particles.
[0149] For condition (2), the lithium-rich manganese-based core is composed of N primary particles, N≥2, and the average particle size of the primary particles is 0.1~1.0μm.
[0150] The particle size of primary particles in the lithium-rich manganese-based core can be obtained by statistical electron microscopy (SEM) imaging. The specific testing method includes: selecting representative scanning electron microscopy (SEM) or transmission electron microscopy (TEM) images; randomly selecting no fewer than 100 independent primary particles from the images; using specialized image analysis software to measure the particle size of each particle individually and calculating the arithmetic mean, which is then used as the particle size of the primary particle. Transmission electron microscopy reveals that the lithium-rich manganese-based core is composed of aggregates of multiple primary particles, where the average particle size includes, but is not limited to, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, or any combination thereof.
[0151] By controlling the primary particles to be uniformly distributed within the range of 0.1-1.0 μm, it is beneficial to shorten and homogenize the diffusion path of lithium ions in the solid phase, while promoting the formation of a dense and stable agglomeration structure inside the secondary particles, thereby improving the compaction density and charge transport uniformity of the material.
[0152] For condition (3), the specific surface area of the positive electrode active material is 1~4m². 2 / g.
[0153] The specific surface area of positive electrode active materials can be detected using methods commonly used in the field, such as nitrogen adsorption.
[0154] Specifically, the specific surface area of the positive electrode active material includes, but is not limited to, 1 m². 2 / g, 1.5m 2 / g、2m 2 / g, 2.5m 2 / g、3m 2 / g, 3.5m 2 / g、4m 2 / g or a range consisting of any two of them.
[0155] The specific surface area of the positive electrode active material is 1m². 2 / g-4m 2 / g, a moderate specific surface area can provide more lithium-ion insertion / extraction active sites and a shorter diffusion path, which helps to improve the initial capacity and high-rate charge and discharge performance of the battery, and can also maintain the structural integrity of the material to ensure the long-cycle performance of the battery.
[0156] For condition (4), the powder resistivity of the positive electrode active material is ≥10. -7 S / Cm.
[0157] The resistivity of the positive electrode active material powder can be detected using methods commonly used in the field, such as referring to GB / T45324-2025 "Determination of Powder Resistivity of Positive Electrode Materials for Lithium-ion Batteries".
[0158] Specifically, the resistivity of the positive electrode active material powder includes, but is not limited to, 10⁻⁶. -7 S / Cm, 2×10 -7 S / Cm, 3×10 -7 S / Cm, 4×10 -7 S / Cm, 5×10 -7 S / Cm, 6×10 -7 S / Cm, 7×10 -7 S / Cm, 8×10 -7 S / Cm, 9×10 -7 S / Cm or any other ≥10 -7 The range of S / Cm.
[0159] When the resistivity of the positive electrode active material powder is within the above range, it can ensure the efficient and smooth conduction of electrons inside the battery in the positive electrode material, avoid the increase in internal resistance of the battery due to excessive resistivity, reduce material aging and structural damage caused by local overheating during cycling, delay battery capacity decay, and extend battery cycle life.
[0160] In another aspect, the present invention provides a lithium-ion secondary battery, including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector in the thickness direction, the positive active layer including a positive active material; the positive active material includes the positive active material as described above.
[0161] Lithium-ion secondary batteries include any one of the following: all-solid-state batteries, semi-solid-state batteries, and liquid batteries.
[0162] When the above-mentioned lithium-ion secondary battery is used, the positive active material in the positive active layer is introduced into the above-mentioned positive active material, so that the positive particle has high structural stability and its surface has good ion transport adaptability, thereby balancing capacity performance and structural maintenance during charging and discharging.
[0163] It is conceivable that the battery provided by this invention includes a negative electrode in addition to the aforementioned positive electrode.
[0164] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector.
[0165] This invention does not strictly limit the negative electrode active material in the negative electrode sheet. It can be a negative electrode active material commonly used in batteries, such as at least one of graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (as an example, it can include silicon suboxide, silicon-carbon materials, silicon-oxygen materials, elemental silicon, etc.), tin-based negative electrode materials (mainly including tin, tin alloys, etc.).
[0166] In some embodiments, the battery described above can be a solid-state battery, which includes a solid electrolyte. Compared to other types of batteries, solid-state batteries offer advantages such as high safety, high energy density, and long cycle life, and are widely used in consumer electronics, power equipment, and energy storage devices. However, in related technologies, the solid-solid contact between the positive electrode material and the solid electrolyte in the solid-state battery cathode suffers from problems such as insufficient contact area, inadequate density, difficulty in ion transport, and high interfacial impedance, resulting in more severe issues with poor rate performance in solid-state batteries.
[0167] In some specific embodiments, the solid electrolyte membrane can be independently disposed between the positive electrode and the negative electrode, or it can be disposed on the surface of the positive electrode and / or the negative electrode. For example, the solid electrolyte membrane can be transferred to the surface of the positive electrode and / or the negative electrode by conventional hot pressing process.
[0168] Specifically, the solid electrolyte membrane includes a solid electrolyte. The solid electrolyte in this embodiment of the invention can be a conventional solid electrolyte in the art, and there are no particular limitations. For details, please refer to the types of solid electrolytes used in the aforementioned positive electrode sheet; further details will not be repeated here.
[0169] It should be noted that the battery provided in the embodiments of the present invention can be prepared by conventional techniques in the art, and there are no particular limitations thereto. For example, the battery preparation process may include the following steps: transferring a solid electrolyte onto a negative electrode sheet, stacking it with the aforementioned positive electrode sheet, then isostatically pressing the resulting laminated structure, and finally encapsulating the electrode sheet into a casing to obtain the battery.
[0170] Furthermore, the battery provided by this invention can also be a liquid battery or a semi-solid battery. In the embodiments of this invention, the specific composition and preparation method of the liquid battery or semi-solid battery can be conventional designs in the art, and no special limitations are imposed thereon.
[0171] The following detailed description of the positive electrode active material and lithium-ion secondary battery provided by the present invention is provided through specific embodiments.
[0172] Example 1
[0173] The method for preparing the positive electrode active material provided in this embodiment includes the following steps:
[0174] 1. Prepare a mixed salt solution of NiSO4, CoSO4, and MnSO4 as solution A; a mixed alkaline solution of NaOH and NH3•H2O, along with sodium borate and sodium phosphate, as solution B; and a mixed alkaline solution of NaOH and NH3•H2O as solution C. The total metal ion concentration of the salt solutions is 2 mol / L, the molar concentration of NaOH is 4 mol / L, and the molar concentration of NH3•H2O is 0.2 mol / L. Add a certain amount of deionized water to the reactor, and use a peristaltic pump to pump solution A into the reactor at a feed rate of 200 ml / h. Control the stirring speed at 1000 rpm and the circulating water temperature at 4 °C. The feed rate of alkali solution B was adjusted using a three-stage speed control at 0-50℃, with the three speeds being 180ml / h, 200ml / h, and 220ml / h, respectively, so that the average feed rate of solution B was controlled at 200ml / h. In addition, alkali solution C was pumped into alkali solution B using a peristaltic pump, with the feed rate of solution C consistent with that of solution B, to achieve the purpose of gradient doping of polyanions from the inside to the outside and from high to low in the synthesis reaction. The pH of the solution system was controlled at 11.0, and the feeding time was 12h. After the reaction was completed, the slurry was subjected to solid-liquid separation, centrifuged and washed with deionized water, and then dried at 120℃ for 24h to obtain the first precursor.
[0175] 2. Mix the first precursor and LiOH•H2O, controlling n(Li):n(Me) = 1.6:1, where Me is Ni, Co, or Mn. After uniform mixing, place the mixture in a muffle furnace. First, raise the temperature to 500℃ at 1℃ / min and hold for 300 min. Then, raise the temperature to 850℃ at 2℃ / min and hold for 600 min. Finally, raise the temperature to 930℃ at 1℃ / min and hold for 300 min. After sintering, remove the material and grind it to obtain a lithium-rich manganese-based core.
[0176] 3. Mix 20g of the above-mentioned lithium-rich manganese-based core and 0.1g of fast ion conductor. After mixing evenly, place the mixture in a muffle furnace, heat to 670℃ at 2℃ / min, and sinter for 600min to obtain the finished positive electrode active material. The preparation methods of the positive electrode active materials provided in Examples 1-26 and Comparative Examples 1-5 are basically the same as those in Example 1, except that the types and proportions of raw materials, processing parameters, etc., are different in each step, as detailed in Table 1.
[0177] Table 1
[0178]
[0179] Note: In Table 1, " / " indicates that the data or substance does not exist.
[0180] Test case
[0181] The positive electrode active materials provided in all embodiments and comparative examples were tested sequentially.
[0182] I. Physical and Chemical Properties
[0183] 1. Doping test
[0184] Test samples were prepared according to the KBr pressing method. The dried KBr powder was ground evenly in a mortar, and then the dried positive electrode active material powder to be tested was added and ground and mixed thoroughly. The mixed powder was poured into an infrared pressing mold, vacuumed and pressurized, and the pressure was maintained for 1 to 2 minutes before being taken out to make a uniform and transparent sheet.
[0185] Place the blank KBr thin film into an infrared spectrometer to collect the background, then place the prepared sample thin film in it, and scan and collect the infrared absorption spectrum of the sample in the wavenumber range of 4000~400cm⁻¹.
[0186] Finally, the infrared spectrum of the obtained sample is compared with the infrared spectrum of the undoped pure positive electrode active material. By observing the shift in the position of the characteristic absorption peak, the change in the peak shape, and whether new characteristic absorption peaks corresponding to the functional groups of the doped element appear, it can be determined whether the doping element has been successfully incorporated into the crystal structure of the positive electrode active material.
[0187] in, Figure 2 The infrared spectrum of the positive electrode active material provided in Embodiment 1 of the present invention is shown. The 1100 cm⁻¹ region of the visible spectrum... -1 (1100.27 cm) -1 The peak at 872.83 cm⁻¹ is a strong stretching vibration peak of the PO bond, which is attributed to the infrared characteristic position of the PO bond in phosphate; and the peak at 872.83 cm⁻¹ is... -1 The absorption peak at 1400-1600 cm⁻¹ corresponds to the stretching vibration of POP, further confirming the existence of the PO bond. -1 The absorption peaks in the specified range match the deformation vibrations of phosphorus and oxygen, forming a complementary relationship with the aforementioned characteristic peaks, confirming the presence of PO bonds. This indicates that PO4... 3- Polyanion doping was successful.
[0188] 2. Distribution of core element concentrations in lithium-rich manganese-based materials
[0189] First, the fast ion conductor coating layer of the positive electrode active material was removed by chemical stripping. Then, scanning electron microscopy was used for detection, and combined with image analysis, the center of the lithium-rich manganese-based core was determined, and the internal and surface regions were divided.
[0190] The lithium-rich manganese-based core was dissolved in HCl and heated until completely dissolved. The volume was then adjusted to 1 L, and the elemental composition was analyzed using an electron probe microanalysis (EPMA) system. Based on the data, the average concentrations of various substances in the internal and surface regions, as well as the X-ray concentrations, were obtained. 2 The amount of elemental doping, etc.
[0191] The test results are shown in Table 2.
[0192] 3. Particle size distribution of lithium-rich manganese-based core
[0193] With reference to GB / T 19077-2016 "Particle Size Analysis - Laser Diffraction Method", the particle size distribution of the lithium-rich manganese-based core and the positive electrode active material is tested.
[0194] The test results are shown in Table 2.
[0195] Table 2
[0196]
[0197] Note: In Table 2, " / " indicates that the data does not exist or the substance does not exist.
[0198] 4. Scanning electron microscope test
[0199] The particle statistical analysis software supporting the scanning electron microscope is used to distinguish successfully coated particles from uncoated particles according to the contrast / grayscale difference of the coated particles, the proportion of the number of successfully coated particles in all identified particles is counted, the distribution uniformity and coverage integrity of the coating layer are evaluated in an auxiliary manner, and finally the coating rate result of the fast ion conductor coating layer is obtained.
[0200] The test results are shown in Table 3.
[0201] The positive electrode active material is vertically cut, and a flat cross section is obtained by inlaying, grinding and polishing; the prepared cross-section sample is placed in a scanning electron microscope, and after vacuuming, a clear cross-sectional microscopic image of the coating layer is obtained with an appropriate magnification. Using the built-in scale of the image, 3 to 5 evenly distributed test points are selected in each area of the cross-sectional images at different positions, and the thickness value of the coating layer at each test point is read respectively; finally, the arithmetic mean value of all test data is calculated to obtain the average thickness of the fast ion conductor coating layer.
[0202] The test results are shown in Table 3.
[0203] Wherein, Figure 3 is the scanning electron microscope image of the lithium-rich manganese-based core provided in Example 1 of the present invention, and it can be seen from Figure 3 that after doping the polyanion conductor, the morphology of the lithium-rich manganese-based core tends to be elongated.
[0204] Figure 4 is the scanning electron microscope image of the lithium-rich manganese-based core provided in Comparative Example 4 of the present invention, and it can be seen from Figure 4 that the morphology of the lithium-rich manganese-based core without polyanion conductor doping is mainly sheet-like.
[0205] 5. Specific surface area of positive electrode active material
[0206] The specific surface area of the positive electrode active material was tested in accordance with GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method".
[0207] The test results are shown in Table 3.
[0208] 6. Ionic conductivity of the fast ion conductor coating
[0209] The ionic conductivity of the fast ion conductor coating can be detected by a method including the following steps:
[0210] Fast-ion conductor powders (such as oxide and sulfide electrolytes) are pressed into dense circular discs in a mold. The diameter (D) and thickness (L) of the sample are precisely measured to calculate the cross-sectional area A and geometric factor. Blocking electrodes are fabricated on both sides of the sample. After the test system is set up, the test frequency range is set to 1MHz to 0.1Hz, and a small signal perturbation is used under constant temperature conditions. The test is started, and the instrument automatically scans the set frequency range, recording the real part (Z′) and imaginary part (−Z′) of the impedance at each frequency. A complex plane diagram is plotted with the real part Z′ as the horizontal axis and the negative imaginary part −Z′ as the vertical axis to construct an equivalent circuit. The bulk resistance (R) is extracted from the fitting results. b The ionic conductivity is calculated using the following formula:
[0211] σ = L / (R) b *A) Where: σ: ionic conductivity (S / cm), L: sample thickness (cm), A: contact area between electrode and electrolyte (cm²), for circular samples A=π(D / 2) 2 Rb: Bulk resistance (Ω) obtained from the fitting.
[0212] The test results are shown in Table 3.
[0213] 7. Powder resistivity
[0214] The resistivity of the positive electrode active material was tested in accordance with GB / T 45324-2025 "Determination of Powder Resistivity of Positive Electrode Material for Lithium-ion Batteries".
[0215] The specific test results are shown in Table 3.
[0216] Table 3
[0217]
[0218] Note: In Table 3, " / " indicates that the data or substance does not exist.
[0219] II. Electrochemical Performance
[0220] Assemble solid-state batteries using the positive electrode active materials provided in all embodiments and comparative examples, including the following steps:
[0221] (1) Preparation of positive electrode sheet: The positive electrode material, lithium phosphorus sulfur chlorine and conductive carbon black are dry mixed under inert conditions (humidity < 1ppm) in a mass ratio of 60:30:10. The mixture is then ball-milled at 400rpm for 3h. After ball milling, the positive electrode sheet (thickness 120μm) is formed by hot rolling (100℃, 15MPa).
[0222] (2) Preparation of negative electrode: A lithium metal foil with a thickness of 45 μm is polished to Ra≤0.1 μm to obtain a negative electrode.
[0223] (3) Solid electrolyte membrane: Lithium, phosphorus, sulfur, chlorine and polytetrafluoroethylene (PTFE) are mixed and rolled at a mass ratio of 6:1 to obtain a solid electrolyte membrane (thickness of 45μm). The positive electrode and the solid electrolyte membrane are hot-pressed (180℃, 8MPa) to obtain a composite positive electrode-solid electrolyte layer.
[0224] (4) Assembly of all-solid-state battery: The positive electrode, solid electrolyte layer and negative electrode are stacked in sequence to obtain an all-solid-state battery.
[0225] 1. 0.1C Discharge Capacity Test: The test environment temperature was 45℃±1℃. The charge and discharge regimes were as follows: a) High-rate charging: 0.1C, until the voltage ≥ 4.2V; b) Constant-voltage charging: 4.2V, until the current ≤ 0.02mA; c) Rest for 10min; d) High-rate discharging: 0.1C, until the voltage ≤ 1.9V; e) Rest for 10min;
[0226] The test data is shown in Table 4.
[0227] 2. Capacity retention test at 1C cycle: The test environment temperature was 45℃±1℃. The charge and discharge regimes were as follows: a) High-rate charging: 1C, until the voltage ≥ 4.2V; b) Constant-voltage charging: 4.2V, until the current ≤ 0.02mA; c) Rest for 10min; d) High-rate discharging: 1C, until the voltage ≤ 1.9V; e) Rest for 10min; Repeat the above cycle 500 times.
[0228] The test results are shown in Table 4.
[0229] 3. Initial Coulombic Efficiency: After each battery was left to stand at 25°C for 4 hours, the initial charge-discharge capacity was tested. The test conditions were: 0.1C charging to 4.55V, constant voltage charging to 0.025C cutoff, left to stand for 3 minutes, and then discharged at 0.1C to 3.0V. The charge-discharge curves were obtained, and the initial charge specific capacity C0 and initial discharge specific capacity D0 at 4.4~4.55V were recorded respectively. The initial coulombic efficiency was calculated according to D0 / C0.
[0230] The test results are shown in Table 4.
[0231] 4. Rate Performance: The battery was charged and discharged at 25℃ using a battery charge / discharge tester. The charge / discharge regime was as follows: constant current charging at 0.2C to 4.25V, then constant voltage charging at 4.25V until the current decreased to 0.02C, followed by resting for 5 minutes, and then constant current discharging at 0.2C to 2.5V. The discharge capacity Q was recorded. 0.2c After resting for 5 minutes, charge with a constant current of 0.2C to 4.25V, then switch to a constant voltage of 4.25V and charge until the current decreases to 0.02C. After resting for 5 minutes, discharge with a constant current of 1C to 2.5V, and record the discharge capacity Q. 1c The capacity retention rate can be calculated using the following formula:
[0232] 1C discharge rate capacity retention rate = Q 1c / Q 0.2c ×100%
[0233] The test results are shown in Table 4.
[0234] Table 4
[0235]
[0236] As can be seen from Table 4, the positive electrode active material provided in the embodiments of the present invention has excellent structural stability and interface compatibility. When used in batteries, it can significantly improve the 0.1C discharge capacity, cycle capacity retention rate, first efficiency and rate performance of the battery.
[0237] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A positive electrode active material, characterized in that, It includes a lithium-rich manganese-based core and a fast-ion conductor coating layer disposed on at least a portion of the surface of the lithium-rich manganese-based core, wherein the lithium-rich manganese-based core is doped with polyanions; Wherein, the polyanion concentration on the surface of the lithium-rich manganese-based core is C1, and the polyanion concentration at the center of the lithium-rich manganese-based core is C2, where C1 < C2.
2. The positive electrode active material according to claim 1, characterized in that, The sphericity of the lithium-rich manganese-based core is 0.7~0.95; The center of the lithium-rich manganese-based core is Q, and the equivalent radius is R; The lithium-rich manganese-based core includes an internal region and a surface region; Wherein, the inner region is the region with Q as the starting point and 1 / 2R as the radius, and the surface region is the region surrounding the inner region and extending from the surface of the inner region to the surface of the lithium-rich manganese-based core. The average concentration of polyanions in the internal region is A, and the average concentration of polyanions in the surface region is B, where 1 < A: B ≤ 10.
3. The positive electrode active material according to claim 2, characterized in that, A is 4000-10000ppm; B is 1000-5000ppm.
4. The positive electrode active material according to any one of claims 1-3, characterized in that, The surface area coverage of the fast ion conductor coating layer is 1% to 50%; And / or, the average thickness of the fast ion conductor coating layer is 20~40 nm; And / or, the ionic conductivity of the fast ion conductor coating layer is >10. -4 S / cm; And / or, the fast ion conductor coating layer includes at least one of lithium ion conductors, sodium ion conductors, oxygen ion conductors, and proton conductors.
5. The positive electrode active material according to any one of claims 1-4, characterized in that, The chemical composition of the polyanions in the lithium-rich manganese-based core includes (X 1 m O p ) n- ; where X 1 The element includes at least one of P, S, As, Mo, Si, B, W, and Al; m is 1~18, p is 4~42, and n is 2~10.
6. The positive electrode active material according to claim 5, characterized in that, The lithium-rich manganese-based core also includes X 2 Element, the X 2 The element includes at least one of P, B, S, Si, and Ti, wherein X 2 Element and the X 1 The elements are different; The lithium-rich manganese-based core satisfies at least one of the following conditions: (1) Based on the lithium-rich manganese-based core, the X 2 The doping level of the element is 100~6000ppm; (2) The X-rays on the surface of the lithium-rich manganese-based core 2 The element concentration is C3, and the X at the center of the lithium-rich manganese-based core... 2 The concentration of the element is C4, and C3 < C4.
7. The positive electrode active material according to claim 5 or 6, characterized in that, The sphericity of the lithium-rich manganese-based core is 0.7~0.95; The center of the lithium-rich manganese-based core is Q, and the equivalent radius is R; The lithium-rich manganese-based core includes an internal region and a surface region; wherein, the internal region is a region with Q as the starting point and 1 / 2R as the radius, and the surface region is a region surrounding the internal region and extending from the surface of the internal region to the surface of the lithium-rich manganese-based core. X of the internal region 2 The average concentration of the element is a, and the X of the surface region is... 2 The average concentration of the element is b, and 1 < a / b ≤ 10.
8. The positive electrode active material according to claim 7, characterized in that, a is 500~1000ppm, b is 100~500ppm.
9. The positive electrode active material according to any one of claims 1-8, characterized in that, The lithium-rich manganese-based core satisfies at least one of the following conditions: (1) The particle size Dv50 of the lithium-rich manganese-based core is 2~5μm, and the SPAN value is 0.5~1.8; (2) The lithium-rich manganese-based core is composed of N primary particles, where N≥2, and the average particle size of the primary particles is 0.1~1.0μm; (3) The specific surface area of the positive electrode active material is 1~4m². 2 / g; (4) The resistivity of the positive electrode active material powder is ≥10. -7 S / Cm.
10. A lithium-ion secondary battery, comprising a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active layer disposed on at least one surface of the positive current collector in the thickness direction, the positive active layer comprising a positive active material; characterized in that, The positive electrode active material includes the positive electrode active material according to any one of claims 1-9; The lithium-ion secondary battery includes any one of the following: all-solid-state battery, semi-solid-state battery, and liquid battery.